Civil engineering project management - Twort, A. C. (Alan Charles), 1920-
This new edition of Civil Engineering: Supervision and Management updates and revises the best practical guide for on-site engineers. Written from the point of view of the project engineer it details their responsibilities, powers and duties. The book has been fully updated to reflect the latest changes to management practice and new forms of contract. As a practical guide to on-site project management the book is invaluable to practicing engineers. * Practical guide for the on-site engineer * Written in line with the ICE qualification exam guidelines * Revised and updated for the latest forms of contracts.